Implementation Model of Agile Methodologies and Frameworks for the Human Resources Sector - Revilla Llanos, Cinthy P. (2023)
The purpose of this project is to develop a guidance implementation model that allows the use of different agile methodologies and frameworks in the Human Resources (HR) areas. The project will be carried out in phases, with the first phase being research and analysis. During this stage, successful cases, frameworks, agile methodologies, and complementary literature on agility for HR areas will be analyzed. Secondly, a useful reference and detailed consultation model for agile methodologies and frameworks will be designed with the aim of positively impacting the transformation of processes and services handled by HR specialists and leaders. Finally, this model will be validated based on feedback from HR experts who have some level of affinity with agility applied in their areas.